Minimally invasive coronary artery bypass grafting using the skeletonized right gastroepiploic arteryCentral MessagePerspective - Hiroki Sakai, MD; Akihiko Yamauchi, MD, PhD; Kazutoshi Tachibana, MD, PhD; Kaito Masuda, MD; Yoshun Sai, MD; Kunihiko Yoshino, MD; Joji Ito, MD; Kouhei Narayama, MD; Keita Kikuchi, MD, PhD (JTCVS Techniques)
Objective: To evaluate the clinical outcomes of right gastroepiploic artery use in minimally invasive coronary artery bypass grafting. Methods: A total of 428 patients who underwent minimally invasive coronary artery bypass grafting from February 2012 to February 2024 were included into this retrospective cohort study. The selection criteria for right gastroepiploic artery use included satisfactory artery size and length, significant stenosis (99% to 100%) of the right coronary artery, and unsuitable ascending aorta for partial clamping. Results: The study cohort comprised 70 men and 8 women, with an average age of 63.6 ± 10.5 years. The right gastroepiploic artery was used in 18.2% (78 out of 428) of cases, without the aorta being touched in all these cases. Total arterial revascularization was achieved in 93.6% of cases and complete revascularization was achieved in 98.7%. Notable postoperative outcomes included zero in-hospital mortality, an incidence of new-onset atrial fibrillation of 9.0%, and a median intensive care unit stay of 2 days. Surgical site infections occurred in 7.5% of patients. Conclusions: The use of the right gastroepiploic artery in minimally invasive coronary artery bypass grafting is a viable option for achieving total arterial revascularization without touching the ascending aorta, enhancing the rate of optimal clinical outcomes.